INOVASI PEMBELAJARAN BERLANDASKAN PROGRAM ANDROID PADA TEMA TEKS PROSEDUR SISWA KELAS XIDI SMK SUGAR GROUP - Retno Susanti; Muhammad Nurwahidin; Dwi Yulianti (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Writing procedure text aims to make students understand how to do and how to make something with sequential steps. However, students find it difficult to write and develop procedural texts such as the lack of interesting media to support learning in writing procedural texts. Teachers still use environment-based media and lectures. Android-based learning is learning that uses innovative, creative, and interesting learning innovation media. The purpose of this study is to facilitate the interaction of students with the subject matter, students with teachers, and between students. This study uses the SLR method, the data obtained based on observations with the help of article reviews and documentation. The results of the research obtained are learning innovations based on android applications provide many benefits for students in developing ideas and making writings with interesting learning media. With these innovations, teachers and students gain experience in making applications and can be creative in the learning process which of course can utilize technology in learning and meet the achievement of learning objectives so as to make learning interesting and fun for teachers and students.